2021
DOI: 10.1186/s13054-020-03435-y
|View full text |Cite
|
Sign up to set email alerts
|

Duration of diaphragmatic inactivity after endotracheal intubation of critically ill patients

Abstract: Background In patients intubated for mechanical ventilation, prolonged diaphragm inactivity could lead to weakness and poor outcome. Time to resume a minimal diaphragm activity may be related to sedation practice and patient severity. Methods Prospective observational study in critically ill patients. Diaphragm electrical activity (EAdi) was continuously recorded after intubation looking for resumption of a minimal level of diaphragm activity (begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…The current study uses data collected in a study conducted at St. Michael’s Hospital in Toronto, Canada, to detect the timing of resumption of diaphragm activity after intubation. 13 Patients were enrolled between June 2015 and August 2017. Electrical activity of the diaphragm was measured by using an esophageal catheter (neurally adjusted ventilator assist catheter and feeding tube) placed within 12 h after endotracheal intubation and initiation of mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…The current study uses data collected in a study conducted at St. Michael’s Hospital in Toronto, Canada, to detect the timing of resumption of diaphragm activity after intubation. 13 Patients were enrolled between June 2015 and August 2017. Electrical activity of the diaphragm was measured by using an esophageal catheter (neurally adjusted ventilator assist catheter and feeding tube) placed within 12 h after endotracheal intubation and initiation of mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work showed that the later was significantly related to TFdi (R 2 = 0.62). 51 TFdi may be more related to diaphragm electrical activity than the pressure it generates, although within-individual analysis are yet to be performed.…”
Section: Generalization Of Findingsmentioning
confidence: 99%
“…Mechanical ventilation depends on the interaction of three key factors: central respiratory drive, respiratory muscle strength, and the load exerted on the respiratory muscle [18]. EAdi is the sum of action potentials of diaphragmatic muscle bers and is therefore the best index to re ect the central drive [19].…”
Section: Discussionmentioning
confidence: 99%